SALURAN, MARGIN DAN STRATEGI PEMASARAN KOMPETITIF DI UMKM PO BAROKAH UNTUK KOMODITAS SINGKONG - Fitriana, Nisa Hafi Idhoh; Rozci, Fatchur (Agridevina : Berkala Ilmiah Agribisnis, 2023)
The purpose of this study is to identify marketing channels and margins, as well as competitive marketing strategies, used by UMKM PO Barokah located in Sidoarjo. The method used in this study is a qualitative method that collects data through interviews and analyzes the basis of interpretation of previous studies. The results of this study indicate that the PO Barokah MSME marketing channel is at the fourth level, and has a marketing margin of Rp. 351,500. Marketing margins have an important role for an MSME in carrying out its competitive strategy. PO Barokah MSME owners also use competitive marketing strategies to enhance business development and attract consumers, such as setting low prices, creating several variations of sinom packaging, focusing on herbal products made at home, highlighting product flavors that are different from ordinary sinom herbs, and collaborated with several hawker sellers and grocery stores. Therefore, the collaborations that are owned are very diverse and beneficial for the business. DOI : https://doi.org/10.33005/agridevina.v12i1.4029